Low-density, high-welding-strength and high-laser-transmittance polypropylene composite material for automobile hard-plastic instrument board and preparation method of low-density, high-welding-strength and high-laser-transmittance polypropylene composite material
By using composite filling technology of long-chain branched polypropylene and homemade functional masterbatch in polypropylene composite materials for automotive dashboards, the material's shortcomings in low-temperature toughness, laser transmittance and welding strength are solved, and the comprehensive performance of low density, high welding strength and high laser transmittance is achieved.
Patent Information
- Application Number
- CN202411978439.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing polypropylene composite materials for automotive dashboards have shortcomings in low-temperature toughness and laser transmittance, and it is difficult to take into account the lightweight and welding strength of the materials.
Long-chain branched polypropylene is used to combine metallocene copolymer polypropylene, and the ratio of the two functional masterbatches is adjusted to optimize material performance by composite filling by homemade magnesium sulfate whisker functional masterbatches and talc powder functional masterbatches.
Polypropylene composite material for automotive hard plastic instrument panels with low density, high welding strength and high laser transmittance is suitable for automotive parts that require laser weakening and vibration friction welding assembly.
Smart Images

Figure BDA0005220970840000071 
Figure BDA0005220970840000081 
Figure BDA0005220970840000082
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials for automobile interior decoration, and in particular to a polypropylene composite material for automobile hard plastic instrument panel with low density, high welding strength and high laser transmittance and a preparation method thereof. Background Art
[0002] As a general polymer material, polypropylene is widely used in automotive interior and exterior decoration due to its low price, good processing performance, balanced mechanical properties, non-toxic and odorless.
[0003] With the diversity of automobile design and the development of vehicle technology, cars have become a common tool for daily travel, and people have higher and higher requirements for automobile comfort, aesthetic design, and safety. As an important part of the car, the dashboard integrates multiple functions and plays a role in protecting the driver's personal safety in the event of an accident. Patent CN106280013A discloses a polypropylene composite material suitable for seamless airbag dashboards, but does not evaluate the limit of the material's low-temperature toughness -35°C notched impact strength performance, nor does it further explore the material products; Patent CN115368701A discloses a laser-weldable magnesium sulfate whisker modified polypropylene composite material, but does not evaluate the physical properties of the material; Patent CN1 11763399A discloses a magnesium sulfate whisker filled polypropylene composite material for automobile dashboards, but does not further explore the performance of the material products. Summary of the invention
[0004] The purpose of the present invention is to develop a polypropylene composite material with low density, high welding strength and high laser transmittance for automotive hard plastic instrument panel parts requiring laser weakening and vibration friction welding assembly requirements. The preparation method of the material is relatively simple and mature, which is conducive to large-scale production.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] A polypropylene composite material for automobile hard plastic instrument panel with low density, high welding strength and high laser transmittance, which is composed of the following raw materials in parts by weight:
[0007] Metallocene copolymer polypropylene: 30-50wt%
[0008] Long chain branched polypropylene: 10-20wt%
[0009] Magnesium sulfate whisker functional masterbatch: 12~25wt%
[0010] Talc functional masterbatch: 12~25wt%
[0011] Toughening agent: 15-20wt%
[0012] Black masterbatch: 1wt%
[0013] Other additives 0.1-3wt%
[0014] The melt index (230°C, 2.16kg) of the metallocene copolymerized polypropylene is about 30-60g / 10min; and the melting point (20°C / min) is ≤150°C.
[0015] The branching degree of the long-chain branched polypropylene is 0.1-0.4; the melt index (230°C, 2.16kg) is about 1-4g / 10min.
[0016] The magnesium sulfate whisker functional masterbatch is prepared as follows:
[0017] 17.6 parts of metallocene copolymerized polypropylene, 80 parts of magnesium sulfate whiskers and 2.4 parts of dispersant are mixed in a high-speed mixer for 3-5 minutes to obtain a mixture, and the mixture is extruded and granulated in a single screw extruder to obtain a magnesium sulfate whisker functional masterbatch. The melt index (230°C, 2.16kg) of the metallocene copolymerized polypropylene is about 25N40g / 10min, and the melting point (20°C / min) is ≤150°C; the magnesium sulfate whiskers are clustered, with an average length of 20-40μm and an average diameter of <1.0μm; and the dispersant is magnesium stearate.
[0018] The talc functional masterbatch is prepared as follows:
[0019] 18.5 parts of metallocene copolymerized polypropylene, 80 parts of talc powder and 1.5 parts of lubricant are mixed in a high-speed mixer at high speed for 3-5 minutes and at low speed for 1-2 minutes to obtain a mixture, and the mixture is extruded and granulated in a single screw extruder to obtain a talc powder functional masterbatch. The melt index (230°C, 2.16kg) of the metallocene copolymerized polypropylene is about 25N40g / 10min, and the melting point (20°C / min) is ≤150°C; the average particle size of the talc powder is 5000-7000 mesh, and the lubricant is calcium stearate.
[0020] The toughening agent is one or both of ethylene-butene copolymer and ethylene-octene copolymer.
[0021] The other auxiliary agents are main antioxidants, auxiliary antioxidants, and light stabilizers, wherein the main and auxiliary antioxidants are one or more complexes such as 1010, antioxidant 168, antioxidant DSTP, etc., and the light stabilizer is hindered amine complex 5229.
[0022] A polypropylene composite material for automobile hard plastic instrument panel with low density, high welding strength and high laser transmittance, wherein the preparation steps are as follows:
[0023] A. Preparation of magnesium sulfate whisker functional masterbatch
[0024] Mix metallocene copolymerized polypropylene, magnesium sulfate whisker and dispersant in different weight fractions in a high-speed mixer for 3-5 minutes to obtain a mixture, extrude and granulate the mixture in a single-screw extruder to obtain a magnesium sulfate whisker functional masterbatch.
[0025] B. Preparation of talc functional masterbatch
[0026] Mix metallocene copolymerized polypropylene, talc and lubricant in different weight fractions in a high-speed mixer at high speed for 3-5 minutes and at low speed for 1-2 minutes to obtain a mixture, extrude and granulate the mixture in a single-screw extruder to obtain a talc functional masterbatch.
[0027] C. Preparation of a polypropylene composite material for automotive hard plastic instrument panel with low density, high welding strength and high laser transmittance
[0028] (1) first weighing metallocene copolymer polypropylene, long-chain branched polypropylene, talc functional masterbatch, toughening agent, black masterbatch and other additives according to weight proportions, and homogenizing them in a high-speed mixer to obtain a mixed raw material;
[0029] (2) The mixed raw materials are placed in the main feeding bin of the intermeshing co-rotating twin-screw extruder, the magnesium sulfate whisker functional masterbatch is placed in the side feeding bin of the intermeshing co-rotating twin-screw extruder, and added into the barrel of the extruder through the side feeding screw, and processed by melt extrusion, cooling, granulation, and drying to obtain a polypropylene composite material for automotive hard plastic instrument panel with low density, high welding strength, and high laser transmittance. Among them, the diameter of the extruder screw is 35mm, the aspect ratio L / D is 48, and the temperature setting of each zone of the main barrel is: zone 1: 180-200℃, zone 2: 205-215℃, zone 3: 215-220℃, zone 4: 210-225℃. The main engine speed is 550-650r / min, the main engine barrel vacuum degree is -0.06~0.1MPa, and the drying time of the three-stage drying tank is 130℃×5h.
[0030] In this scheme, although the high and low temperature toughness and laser transmittance of the inorganic-filled modified polypropylene composite material are improved, and the possibility of application in hard plastic instrument panels is described; however, the improvement direction is often relatively single, either for material toughness or laser transmittance, and no consideration and evaluation are made on the lightweight of the polypropylene composite material for hard plastic instrument panels, the welding strength with the TPO airbag frame, and the laser transmittance of the material. The present invention adopts long-chain branched polypropylene compounded with metallocene copolymerized polypropylene, and composite filling is performed by self-made magnesium sulfate whisker functional masterbatch and talcum powder functional masterbatch, while achieving low density and high toughness, the vibration friction welding strength and laser transmittance of the material are improved, and the laser transmittance can be adjusted by adjusting the ratio of the two functional masterbatches, which has a high application value on automotive hard plastic instrument panels.
[0031] The benefits of the present invention are as follows: the present invention adopts long-chain branched polypropylene compounded with metallocene copolymerized polypropylene, and compositely fills with self-made magnesium sulfate whisker functional masterbatch and talcum powder functional masterbatch, thereby achieving low density and high toughness while improving the vibration friction welding strength between the material and the TPO airbag frame and the laser transmittance of the material, and the laser transmittance of the material can be adjusted by adjusting the ratio of the two functional masterbatches, and has high application value on automobile hard plastic instrument panels. DETAILED DESCRIPTION
[0032] The present invention can be further described by the following preferred embodiments, but these embodiments are only for illustration and do not limit the scope of the present invention.
[0033] In the composite material formula of the embodiment and the comparative example, the metallocene copolymer polypropylene resin in the composite material is provided by Total Company, and the trade name is MR60MC2 and MR30MC2. Long-chain branched polypropylene is provided by Borealis Chemical, and the trade name is WB140. Magnesium sulfate whiskers are provided by Yingkou Wesk Chemical Company, and the trade name is WS-3D. Talc is provided by Liaoning Aihai Company, and the trade name is: CHX05L. Toughener is provided by Dow Chemical, and the trade name is 8842. Dispersant and lubricant are provided by Hanwei Company. Black masterbatch is provided by Cabot Corporation, and the trade name is E320. Main and auxiliary antioxidants are provided by BASF and British ICE Company, and the trade names are Irganox 1010, Irgafos 168 and Negonox DSTP, and light stabilizer is provided by Liansheng Technology Co., Ltd., and the trade name is 5229.
[0034] The test methods of the embodiments and comparative examples are as follows: density is tested according to ISO 1183. Melt index is tested according to ISO 1133. Tensile strength is tested according to ISO 527-2. Flexural modulus is tested according to ISO 178. Charpy notched impact strength is tested at 23°C and -35°C according to ISO 179-1.
[0035] The welding strength test method of the embodiment and the comparative example is to cut the injection molded 170×10×4mm tensile specimen and the same size TPO injection molded specimen, and then test the fracture strength according to ISO 527-2. The vibration friction welding process is as follows: welding frequency 50-80Hz, welding pressure 30-50bar, welding amplitude 2.6-3.4mm, welding time 3N5s, welding depth 0.9N1.1mm.
[0036] The high laser transmittance test method of the embodiment and the comparative example is to place the injection molded 390×275×3mm sample on the tooling, and obtain a rounded rectangular weakened area through laser weakening by a laser weakening device, intercept the weakened area, and measure the residual thickness of the sample after weakening and cutting on an optical microscope. The parameters of the weakening device are: laser wavelength 10.6μm, rated power 450~2000w, laser on-off time 0.25ms, and closed-loop control sensor specified voltage 1.3V. The optical microscope magnification is 50x.
[0037] The specific preparation methods and weight proportions of the embodiments and comparative examples are as follows:
[0038] A. Preparation of magnesium sulfate whisker functional masterbatch
[0039] Mix metallocene copolymerized polypropylene, magnesium sulfate whisker and dispersant in different weight fractions in a high-speed mixer for 3-5 minutes to obtain a mixture, extrude and granulate the mixture in a single-screw extruder to obtain a magnesium sulfate whisker functional masterbatch.
[0040] B. Preparation of talc functional masterbatch
[0041] Mix metallocene copolymerized polypropylene, talc and lubricant in different weight fractions in a high-speed mixer at high speed for 3-5 minutes and at low speed for 1-2 minutes to obtain a mixture, extrude and granulate the mixture in a single-screw extruder to obtain a talc functional masterbatch.
[0042] C. Preparation of a polypropylene composite material for automotive hard plastic instrument panel with low density, high welding strength and high laser transmittance
[0043] (1) First, weigh metallocene copolymer polypropylene, long-chain branched polypropylene, talc functional masterbatch, toughening agent, black masterbatch and other additives according to the following weight parts, and homogenize them in a high-speed mixer to obtain a mixed raw material;
[0044] (2) The mixed raw materials are placed in the main feeding bin of the intermeshing co-rotating twin-screw extruder, the magnesium sulfate whisker functional masterbatch is placed in the side feeding bin of the intermeshing co-rotating twin-screw extruder, and added into the barrel of the extruder through the side feeding screw, and processed by melt extrusion, cooling, granulation, and drying to obtain a polypropylene composite material for automotive hard plastic instrument panel with low density, high welding strength, and high laser transmittance. Among them, the diameter of the extruder screw is 35mm, the aspect ratio L / D is 48, and the temperature setting of each zone of the main barrel is: zone 1: 180-200℃, zone 2: 205-215℃, zone 3: 215-220℃, zone 4: 210-225℃. The main engine speed is 550-650r / min, the main engine barrel vacuum degree is -0.06~0.1MPa, and the drying time of the three-stage drying tank is 130℃×5h.
[0045] Table 1 Weight parts of Examples 1-4 and Comparative Examples 1-3
[0046]
[0047]
[0048] Table 2 Performance test results of Examples 1-4 and Comparative Examples 1-3
[0049]
[0050] It can be seen from the comparison of the test results of Examples 1, 2, 3, 4 and Comparative Examples 1, 2, 3. As the compounding ratio of magnesium sulfate whisker functional masterbatch increases, the density of the polypropylene composite material gradually decreases, and accordingly, the residual thickness after laser weakening shows an increasing trend. According to the working principle of the laser weakening equipment, when the working sensor senses the rated voltage of the laser, the laser stops emitting. It can be seen that the greater the residual thickness of the sample, the higher the laser transmittance of the corresponding material. By comparing with Comparative Example 3, by increasing the content of long-chain branched polypropylene, the welding strength of the interface is significantly increased after vibration friction welding. It can be seen from the examples and comparative examples that, considering the high and low temperature toughness, density, welding strength, and laser transmittance of the material, the polypropylene composite material material obtained in Example 1 achieves a relatively ideal low density and high welding strength under the same filler amount and maintains a high high and low temperature toughness, and at the same time has a high laser transmittance.
[0051] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined by the claims.
Claims
1. A polypropylene composite material for automobile hard plastic instrument panel with low density, high welding strength and high laser transmittance, characterized in that: It is composed of the following raw materials in percentage by mass: Metallocene copolymer polypropylene: 30-50wt%; Long chain branched polypropylene: 10-20wt%; Magnesium sulfate whisker functional masterbatch: 12-25wt%; Talc functional masterbatch: 12~25Wt%; Toughening agent: 15-20wt%; Black masterbatch: 1wt%; Other additives 0.1-3wt%.
2. The polypropylene composite material for automobile hard plastic instrument panel with low density, high welding strength and high laser transmittance according to claim 1, characterized in that: The melting index of the metallocene copolymerized polypropylene is 20-60 g / 10 min; the melting point (20° C. / min) of the copolymerized polypropylene is ≤150° C.
3. The polypropylene composite material for automobile hard plastic instrument panel with low density, high welding strength and high laser transmittance according to claim 1, characterized in that: The branching degree of the long-chain branched polypropylene is 0.1-0.4, and the melt index is 0.5-5 g / 10 min.
4. The polypropylene composite material for automobile hard plastic instrument panel with low density, high welding strength and high laser transmittance according to claim 1, characterized in that: The magnesium sulfate whisker functional masterbatch is prepared from the following components in parts by weight: 17.6 parts of metallocene copolymerized polypropylene, 80 parts of magnesium sulfate whiskers, and 2.4 parts of a dispersant. The melt index of the metallocene copolymerized polypropylene is 25-40 g / 10 min, and the melting point (20° C. / min) is ≤150° C. The magnesium sulfate whiskers are cluster-shaped, with an average length of 20-40 μm and an average diameter of <1.0 μm, and the dispersant is magnesium stearate.
5. The polypropylene composite material for automobile hard plastic instrument panel with low density, high welding strength and high laser transmittance according to claim 1, characterized in that: The talc functional masterbatch is prepared from the following components in parts by weight: 18.5 parts of metallocene copolymerized polypropylene, 80 parts of talc powder, and 1.5 parts of lubricant. The melt index of the metallocene copolymerized polypropylene is about 25-40 g / 10 min, and the melting point (20°C / min) is ≤150°C, the average particle size of the talc powder is 5000-7000 mesh, and the lubricant is calcium stearate.
6. The polypropylene composite material for automobile hard plastic instrument panel with low density, high welding strength and high laser transmittance according to claim 1, characterized in that: The toughening agent is one or both of ethylene-butene copolymer and ethylene-octene copolymer.
7. The polypropylene composite material for automobile hard plastic instrument panel with low density, high welding strength and high laser transmittance according to claim 1, characterized in that: The other auxiliary agents are a main antioxidant, a secondary antioxidant and a light stabilizer, wherein the main antioxidant is a hindered phenol or a thioester, the secondary antioxidant is a phosphite, and the light stabilizer is a hindered amine.
8. The method for preparing the polypropylene composite material for automobile hard plastic instrument panel with low density, high welding strength and high laser transmittance according to any one of claims 1 to 7, characterized in that: The steps include: A. Preparation of magnesium sulfate whisker functional masterbatch Mix the weight fractions of metallocene copolymerized polypropylene, magnesium sulfate whiskers, and dispersant in a high-speed mixer for 3-5 minutes to obtain a mixture, extrude and granulate the mixture in a single-screw extruder to obtain a magnesium sulfate whisker functional masterbatch; B. Preparation of talc functional masterbatch Mix metallocene copolymerized polypropylene, talc and lubricant in a high-speed mixer at a high speed for 3-5 minutes and at a low speed for 1-2 minutes to obtain a mixture, extrude and granulate the mixture in a single-screw extruder to obtain a talc functional masterbatch; C. Preparation of a polypropylene composite material for automotive hard plastic instrument panel with low density, high welding strength and high laser transmittance (1) first weighing metallocene copolymer polypropylene, long-chain branched polypropylene, talc functional masterbatch, toughening agent, black masterbatch and other additives according to weight proportions, and homogenizing them in a high-speed mixer to obtain a mixed raw material; (2) The mixed raw materials are placed in the main feeding bin of an intermeshing co-rotating twin-screw extruder, the magnesium sulfate whisker functional masterbatch is placed in the side feeding bin of the intermeshing co-rotating twin-screw extruder, and added into the barrel of the extruder through the side feeding screw, and processed by melt extrusion, cooling, granulation, and drying to obtain a polypropylene composite material for automotive hard plastic instrument panel with low density, high welding strength, and high laser transmittance; wherein the extruder screw diameter is 35 mm, the aspect ratio L / D is 48, and the temperature setting of each zone of the main barrel is: zone 1: 180-200°C, zone 2: 205-215°C, zone 3: 215-220°C, zone 4: 210-225°C. The main barrel speed is 550-650r / min, the main barrel vacuum degree is -0.06-0.1MPa, and the drying time of the three-stage drying tank is 130°C×5h.
Citation Information
Patent Citations
Polypropylene composition for seamless airbag dashboard and preparation method of polypropylene composition
CN106280013A
Automotive high-rigidity and high-toughness polypropylene composite material and preparation method thereof
CN106273350A
Polypropylene composite material used for dashboards and interior parts of automobiles, and preparation method thereof
CN108219277A
Polypropylene-basic magnesium sulfate whisker composite material for thin-wall automotive product
CN110003572A
Low-odor and low-VOC microcellular foaming modified polypropylene material and preparation method thereof
CN112080076A